HUBUNGAN JENIS KELAMIN DAN JALUR PENERIMAAN DENGAN SELF DIRECTED LEARNING READINESS PADA MAHASISWA ANGKATAN 2012 FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Agung, Adhisti Handarie; ", Zulharman; Hamidy, Muhammad Yulis (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Self Directed Learning Readiness (SDLR) is important both for students and universities to accomplish certain learning objectives. There are internal and external factors influencing SDLR, such as gender and entry method of the students to the faculty.Genderdefined as male and female while entry methode defined SNMPTN, SNMPTN Undangan, PBUD and PBUD Bina Lingkungan. This research aimed to seek a relationship between gender and entry method to SDLR of Faculty of Medicine, University of Riau Year 2012 Students. This research built as analitical research with cross sectional basis and using total sampling method. using a questionaire developed by Zulharman ( 2006). This research found most of Faculty of Medicine, University of Riau Year 2012 Students (65 %) has a middle scored SDLR, on gender basis female students has better SDLR score (132,13) compared to males (130,52). while on entry method basis the PBUD entry method students has better SDLR score (138) compare to SNMPTN (132), SNMPTN Undangan (123), and PBUD Bina Lingkungan (133. The relationships analyzed by Kolmogorof-Smirnov statistical method, with the relationship of Gender to SDLR had a P-Value = 0.265 while the relationship of entry method to SDLR had a P-Value = 0.181. Those P-Values > α (0.05) meaning there are no relationship of gender and entry method to SDLR rating of Faculty of Medicine, University of Riau Year 2012 Students.Keywords: Self Directed Learning Readiness, SDLR, Gender, Entry Method